2012
DOI: 10.3382/ps.2011-01628
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of heat shock protein 70 and its relationship to intestine under acute heat stress in broilers: 2. Intestinal oxidative stress

Abstract: Oxidative stress injury is one important factor in intestinal mucosal barrier damage. Expression of heat shock protein (HSP)70 is an endogenous mechanism by which living cells adapt to stress. This study was undertaken to investigate the protective effects of HSP70 on intestinal oxidative stress. Two hundred and forty broilers were injected intraperitoneally with HSP70 inducer l-(1)-glutamine or with the inhibitor quercetin. Twenty-four hours later, they were heat stressed for 0, 2, 3, 5, and 10 h, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
114
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 41 publications
9
114
0
2
Order By: Relevance
“…Fukata & Abreu (2007) demonstrated that TLR4 induces the activation of cyclooxygenase 2 and prostaglandin E2 in vitro and in vivo, which are important for cell proliferation and apoptosis in response to intestinal mucosal injury. Gu et al (2012) indicated that HSP70 is capable of protecting the intestinal mucosa from heat stress injury by enhancing the antioxidant capacity of broilers. Furthermore, TLR4 is involved in the recognition of endogenous or exogenous products of microbes, such as heat shock protein (HSP) and lipopolysaccharide (LPS) (Ohashi et al, 2000;Vabulas et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fukata & Abreu (2007) demonstrated that TLR4 induces the activation of cyclooxygenase 2 and prostaglandin E2 in vitro and in vivo, which are important for cell proliferation and apoptosis in response to intestinal mucosal injury. Gu et al (2012) indicated that HSP70 is capable of protecting the intestinal mucosa from heat stress injury by enhancing the antioxidant capacity of broilers. Furthermore, TLR4 is involved in the recognition of endogenous or exogenous products of microbes, such as heat shock protein (HSP) and lipopolysaccharide (LPS) (Ohashi et al, 2000;Vabulas et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data from HS and endotoxin shock models (Ryan et al, 1994) support the critical role of the liver in the response to thermal and endotoxin challenge. During HS, a disturbance in the microecological balance of the intestinal flora may cause bacterial translocation and induce the production of intestinal endotoxins (Gu et al, 2012;Yu et al, 2013), allowing large amounts of endotoxins to reach the liver. TLR4 is stably expressed on the surface of many cells, including the Kupffer cells of the liver (Zuo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…They act as cytoprotective proteins and are having the ability to upsurge stress tolerance and enhance survival rates of heat stressed birds (Latchman, 2001). It has been reported that HSP mRNA expression is increased in birds that are exposed to stress rather than those that are kept at thermoneutral zone (Gu et al, 2012). It has also been reported that some supplementations can also regulate expression of HSP (Sahin et al, 2012) 54.…”
Section: Resultsmentioning
confidence: 97%
“…Under conditions of thermostress, HSP70 synthesis is increased in order to protect the circulatory system from serious injury (Hartl, 1996;Gu et al, 2012). However, changes in gene expression for other reasons should also be considered, as they may not be associated with changes in the activity of gene products.…”
Section: Discussionmentioning
confidence: 99%